VD_FINDINFO HC / 2016 / 115 vom 28. Oktober 2015 - VD Tribunal cantonal (2015)
CONTRAT DE TRAVAIL, RÉSILIATION IMMÉDIATE, JUSTE MOTIF, BAGARRE | 337 al. 1 CO, 337 al. 2 CO, 337c al. 1 CO, 337c al. 3 CO